1990
DOI: 10.1002/pros.2990160108
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of genes for basic fibroblast growth factor and transforming growth factor type β2 in human benign prostatic hyperplasia

Abstract: It is now widely accepted that factors other than androgen are crucial in the normal and abnormal growth of the prostate, including human benign prostatic hyperplasia (BPH). Using a Northern blot analysis, we examined human normal and benign hyperplastic prostates for expressions of basic fibroblast growth factor (FGF), acidic FGF, transforming growth factor type beta 2 (TGF-beta 2), TGF-beta 1, and epidermal growth factor (EGF). Basic FGF mRNAs were detectable in all the prostates examined. In addition, level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
2
4

Year Published

1992
1992
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(96 citation statements)
references
References 27 publications
7
81
2
4
Order By: Relevance
“…A twofold increase in FGF2 mRNA in BPH tissues has been observed by Mori and colleagues, 21 consistent with the idea that FGF2 expression is controlled primarily by the level of mRNA in vivo. FGF2 transcription is regulated by a variety of factors in different cell types 14 -16 including cytokines.…”
Section: Discussionsupporting
confidence: 87%
“…A twofold increase in FGF2 mRNA in BPH tissues has been observed by Mori and colleagues, 21 consistent with the idea that FGF2 expression is controlled primarily by the level of mRNA in vivo. FGF2 transcription is regulated by a variety of factors in different cell types 14 -16 including cytokines.…”
Section: Discussionsupporting
confidence: 87%
“…They share similar biological properties but present slightly different tissue distribution (Massague, 1990). While TGF-β2 mRNA appears to be increased in BPH (Mori et al, 1990), TGF-β1 mRNA levels have been suggested to be increased in PCA (Merz et al, 1994). Additionally, patients with metastatic PCA displaying high levels of serum IL-6 have also been reported to present increased serum levels of TGF-β1 (Adler et al, 1999).…”
Section: Expression Of Genes Encoding Cytokines In Pca and Bph Tissuesmentioning
confidence: 99%
“…In BPH, the local concentration of bFGF is two-to threefold higher than in normal prostate (9,10). This fact suggests that bFGF is probably involved in BPH.…”
Section: Introductionmentioning
confidence: 96%